The Analysis Scientific Attitudes in the Implementation of Science-Biology Learning Practicum for Class VIII Students in SMPN 34 Padang - Tiffany Mantoviana; Azwir Anhar; Zulyusri Zulyusri; Ristiono Ristiono (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2020)
Scientific attitude is a collection of several important aspects that describe the interaction of each student. This study aims to study the quality of scientific attitudes carried out by students when carrying out practical learning in Natural Sciences-Biology Class VIII SMPN 34 Padang. The aspects of scientific thought discussed include: 1) curiosity, 2) respect for data, 3) critical thinking, 4) discovery and creativity, 5) open thinking and working together, 6) perseverance, and 7) sensitive to Surrounding environment. This type of research is a descriptive study, with a total of 280 students and a sample of 108 students consisting of 9 classes. Sampling using Proportional Cluster Random Sampling technique by taking ± 40% of the total population. Data collection using questionnaires and observation sheets. Data analysis was performed quantitatively with the percentage analysis method. From this study obtained research on scientific quality assessment on every aspect of the aspect curiosity has good criteria, aspects of respect for data that have adequate criteria, critical aspects of thinking have sufficient criteria, aspects of discovery and considerations that have good quality, aspects of open thinking and working together have good criteria, perseverance aspects have good criteria, and aspects that are sensitive to the environment have criteria. So, the quality of scientific thinking of students in the implementation of science-biology learners.